Can skin exposure to sunlight prevent liver inflammation? - Gorman, S.; Black, Lucinda; Feelisch, M.; Hart, P.; Weller, R. (MDPI Publishing, 2015)
Liver inflammation contributes towards the pathology of non-alcoholic fatty liver disease (NAFLD). Here we discuss how skin exposure to sunlight may suppress liver inflammation and the severity of NAFLD. Following exposure to sunlight-derived ultraviolet radiation (UVR), the skin releases anti-inflammatory mediators such as vitamin D and nitric oxide. Animal modeling studies suggest that exposure to UVR can prevent the development of NAFLD. Association studies also support a negative link between circulating 25-hydroxyvitamin D and NAFLD incidence or severity. Clinical trials are in their infancy and are yet to demonstrate a clear beneficial effect of vitamin D supplementation. There are a number of potentially interdependent mechanisms whereby vitamin D could dampen liver inflammation, by inhibiting hepatocyte apoptosis and liver fibrosis, modulating the gut microbiome and through altered production and transport of bile acids. While there has been a focus on vitamin D, other mediators induced by sun exposure, such as nitric oxide may also play important roles in curtailing liver inflammation.